Banking on the Body - Kara W. Swanson (Harvard University Press, 2014)
In 2008 Connie Culp became the fi rst American woman to undergo a face transplant, receiving the mouth, nose, and cheeks of a dead woman. Th e victim of a shotgun blast fi red by her husband, Culp had been severely disfi gured, missing both her nose and the roof of her mouth. After the surgery, she could talk, smile, and smell again, in a dramatic transformation of both her appearance and her quality of life. Her transplant, and earlier face transplants performed in France and China, transformed not only the recipients but all human faces.ï›œ What the ancient Romans knew as â€œthe refl ection of the soul,â€ the face is now a body product that can be harvested from one body for use by another.